Stability of the high-current ion beam in drift gap of linear induction accelerator - Karas, V.I.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2013)
The results of numerical simulation of compensated ion beam (CIB) transport with current density 9 MA/m² through the drift gap of a linear induction accelerator (LIA) are presented. The CIB stability for the three methods of compensation in the charge of the ion beam in the absence and presence of an external magnetic field is considered. It is shown that in the presence of an external magnetic field instabilities development does not lead to a significant deterioration in the ion beam quality regardless of the compensation way. It is shown, that the most effective addition compensation of the ion beam in charge is applying of self-consistent injection of additional electrons, which leads to the conservation of the CIB parameters, sufficient for its use in heavy-ion inertial fusion (HIF). Представлені результати чисельного моделювання транспортування КІП густиною струму 9 МА/м² через дрейфовий проміжок лінійного індукційного прискорювача. Розглянута стійкість КІП для трьох методів компенсації іонного пучка за зарядом при відсутності та наявності зовнішнього магнітного поля. Показано, що при наявності зовнішнього магнітного поля розвиток нестійкостей не призводе до суттєвого погіршення якості іонного пучка незалежно від способу компенсації. Показано, що найбільш ефективною докомпенсацією іонного пучка за зарядом є застосування самоузгодженої інжекції додаткових електронів, що призводить до збереження параметрів КІП, достатніх для його використання у важкоіонному інерціальному синтезі. Представлены результаты численного моделирования транспортировки КИП плотностью тока 9 МА/м² через дрейфовый промежуток линейного индукционного ускорителя. Рассмотрена устойчивость КИП для трех методов компенсации ионного пучка по заряду в отсутствие и при наличии внешнего магнитного поля. Показано, что при наличии внешнего магнитного поля развитие неустойчивостей не приводит к существенному ухудшению качества ионного пучка независимо от способа компенсации. Показано, что наиболее эффективной докомпенсацией ионного пучка по заряду является применение самосогласованной инжекции дополнительных электронов, что приводит к сохранению параметров КИП, достаточных для его использования в тяжелоионном инерциальном синтезе.